2017
DOI: 10.1001/jamacardio.2016.5550
|View full text |Cite
|
Sign up to set email alerts
|

Are Electronic Cigarette Users at Increased Risk for Cardiovascular Disease?

Abstract: Five-year outcome after implantation of zotarolimus-and everolimus-eluting stents in randomized trial participants and nonenrolled eligible patients: a secondary analysis of a randomized clinical trial [published online January 18, 2017]. JAMA Cardiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…For example, exposure to secondhand cigarette smoke has nearly as large an effect on many risk factors for cardiovascular disease and the risk of acute myocardial infarction as does being an active smoker ( 13 ). In addition, e-cigarettes expose users to acrolein and other aldehydes ( 17 , 18 ). Like conventional cigarette smokers, e-cigarette users experience increased oxidative stress ( 26 , 92 ) and increases in the release of inflammatory mediators ( 26 , 61 ).…”
Section: Health Effects Of E-cigarettesmentioning
confidence: 99%
“…For example, exposure to secondhand cigarette smoke has nearly as large an effect on many risk factors for cardiovascular disease and the risk of acute myocardial infarction as does being an active smoker ( 13 ). In addition, e-cigarettes expose users to acrolein and other aldehydes ( 17 , 18 ). Like conventional cigarette smokers, e-cigarette users experience increased oxidative stress ( 26 , 92 ) and increases in the release of inflammatory mediators ( 26 , 61 ).…”
Section: Health Effects Of E-cigarettesmentioning
confidence: 99%
“…Two of the central pillars on which the harm reduction argument rests are: (a) use of ENDS is substantially less harmful than smoking cigarettes and (b) their use leads to higher population-level smoking quit rates [ 6 , 13 , 26 30 ]. Although more research is necessary before the full extent of the risks from ENDS use are known [ 31 , 32 ], the extant research suggests that use of ENDS is likely substantially less harmful than smoking combustible cigarettes [ 25 , 33 – 37 ], with most debate focusing on how much less harmful [ 28 ]. Reduced risk, however, is insufficient for achieving population-level harm reduction without effecting switching from a higher risk to a lower risk product.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the recent Surgeon General’s report on e-cigarettes, nicotine sustains addiction and interferes with typical adolescent brain development (US Department of Health and Human Services, 2016). While there is limited understanding of the health effects of e-liquid constituents, emerging evidence suggests that e-cigarette constituents may pose cardiovascular and respiratory risks (Bhatnagar, 2017; Shields et al, 2017). Further, many recent studies, including our own, have also observed that e-cigarette use progresses to future cigarette use among youth (Bold et al, 2018; Soneji et al, 2017).…”
mentioning
confidence: 99%